Review: Peran Zat Pelicin dalam Meningkatkan Efisiensi Proses Pembutan Sediaan Tablet Oral - Mikdat Adam; Veressa Alfianti; Nisa Aulia Sera; Della Prastyka; Putri Novianur Ramadhani; Nor Latifah (An-Najat, 2024)
The use of lubricants in oral tablet formulations has an important role in improving the efficiency of the production process. The lubricating agent helps to reduce friction between the particles and the mold wall, minimizing the risk of tablet damage during the printing and separation process. The study reviewed different types of lubricants, such as magnesium stearate and stearic acid, as well as their effects on the compactness, crushing time, and release of the active ingredient of the tablets. Optimal formulation is needed to avoid quality degradation due to excessive lubrication. Thus, the selection of the right lubricant is key to ensuring consistent tablet quality and a more efficient production process.